Characterisation of the native lipid moiety of Echinococcus granulosus antigen B. - Gonzalo Obal; Ana Lía Ramos; Valeria Silva; Analía Lima; Carlos Batthyany; María Inés Bessio; Fernando Ferreira; Gustavo Salinas; Ana María Ferreira (Public Library of Science (PLoS), 2012)
Antigen B (EgAgB) is the most abundant and immunogenic antigen produced by the larval stage (metacestode) of Echinococcus granulosus. It is a lipoprotein, the structure and function of which have not been completely elucidated. EgAgB apolipoprotein components have been well characterised; they share homology with a group of hydrophobic ligand binding proteins (HLBPs) present exclusively in cestode organisms, and consist of different isoforms of 8-kDa proteins encoded by a polymorphic multigene family comprising five subfamilies (EgAgB1 to EgAgB5). In vitro studies have shown that EgAgB apolipoproteins are capable of binding fatty acids. However, the identity of the native lipid components of EgAgB remains unknown. The present work was aimed at characterising the lipid ligands bound to EgAgB in vivo. EgAgB was purified to homogeneity from hydatid cyst fluid and its lipid fraction was extracted using chloroform∶methanol mixtures. This fraction constituted approximately 40-50% of EgAgB total mass. High-performance thin layer chromatography revealed that the native lipid moiety of EgAgB consists of a variety of neutral (mainly triacylglycerides, sterols and sterol esters) and polar (mainly phosphatidylcholine) lipids. Gas-liquid chromatography analysis showed that 16∶0, 18∶0 and 18∶1(n-9) are the most abundant fatty acids in EgAgB. Furthermore, size exclusion chromatography coupled to light scattering demonstrated that EgAgB comprises a population of particles heterogeneous in size, with an average molecular mass of 229 kDa. Our results provide the first direct evidence of the nature of the hydrophobic ligands bound to EgAgB in vivo and indicate that the structure and composition of EgAgB lipoprotein particles are more complex than previously thought, resembling high density plasma lipoproteins. Results are discussed considering what is known on lipid metabolism in cestodes, and taken into account the Echinococcus spp. genomic information regarding both lipid metabolism and the EgAgB gene family.